(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
The ongoing pandemic caused by coronavirus disease (COVID-19) is now a global concern. Although SARS-CoV-2 primarily involves lung, there are emerging data on involvement of heart, brain, kidney, gastrointestinal tract, liver and others. Amongst neurological manifestations, acute stroke, encephalitis and GBS are reported. Here we describe two RT-PCR confirmed SARS-CoV-2 infected patients presented with acute ischemic stroke. The possible background mechanisms are arterial thrombosis due to hypercoagulability, direct and immune-mediated neuronal damage, viral vasculopathy, cardio-embolism etc. BSMMU J 2021; 14 (COVID -19 Supplement): 60-63